Analisis Kebutuhan Tenaga Kerja Untuk Meningkatkan Output Produksi Loyang dengan Metode Stopwatch Time Study - Maharani, Olivia Eka; Putri, Erni Puspanantasari; Rosyidiin, Afrigh Fajar (SURYA TEKNIKA, 2025)
UD. Loyang Pan Ikan is a manufacturing industry that has been producing galvalume trays since 2010. The production process is still done manually, involving four workers and producing an average of 4,000 baking sheets per month. Each worker handles more than one work element, which can trigger physical fatigue and impact the increase in standard time as well as the high workload. This research aims to analyze the workload, identify lesseffective activities, and determine the ideal number of workers. The methods used include Stopwatch Time Study to determine standard time, Work Load Analysis (WLA) to measure workload, and Work Force Analysis (WFA) to calculate labor requirements. The analysis results show that Worker 1's workload is 125.22% and Worker 4's is 120.58%, which exceed the normal limits. Therefore, it is recommended to add two more workers to reduce the workload and increase productivity.